Pengaruh Variasi Lama Perendaman dan Suhu Penggilingan terhadap Kadar Protein Susu Kedelai - Mufida , Nadiya Syafiah; Hanwar , Dedi (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Soy milk, an extract from soybeans, significantly contributes to human nutritional needs, particularly as a source of plant-based protein. The protein quality in soy milk is highly influenced by processing parameters, including soybean soaking duration and grinding temperature. This study aimed to determine the optimum combination of soaking time and grinding temperature to maximize soy milk's protein content. The effects of these two factors were evaluated using Response Surface Methodology (RSM) with a Central Composite Design (CCD). Experiments were conducted for 13 experimental combinations, replicated three times. Protein content was determined by the Lowry method, while pH measurements were also performed to monitor quality. Grinding temperatures ranged from 25°C to 80°C and soaking times varied from 6 to 12 hours, using Grobogan soybean variety as the main raw material. Other parameters such as soybean quantity, water volume, soaking temperature, and boiling and grinding times were set as controlled variables. Optimization results using Design-Expert software indicated that the optimum formulation was achieved at a grinding temperature of 61°C and a soaking time of 9 hours 46 minutes. Under these optimum conditions, the resulting soy milk exhibited a protein content of 3.1% (w/w) and a pH of 7.02, both meeting established soy milk quality standards.